2022
DOI: 10.3389/fpls.2022.956936
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability and heritability analysis of sweetpotato weevil resistance, root yield, and dry matter content in sweetpotato

Abstract: Efficient breeding and selection of superior genotypes requires a comprehensive understanding of the genetics of traits. This study was aimed at establishing the general combining ability (GCA), specific combining ability (SCA), and heritability of sweetpotato weevil (Cylas spp.) resistance, storage root yield, and dry matter content in a sweetpotato multi-parental breeding population. A population of 1,896 F1 clones obtained from an 8 × 8 North Carolina II design cross was evaluated with its parents in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…Another study revealed similar results (with H 2 =0.49%) and further showed that additive effects contributed the most to SPW resistance and HCA concentration [51]. More recently, a narrow sense heritability (h 2 =0.30) was reported for SPW resistance based on a relatively high population [52]. We hope that the adoption of modern experimental designs such as the row-column designs, which use more replications for field phenotyping, will enable estimation of higher heritability values for SPW resistance for future genomic analyses.…”
Section: The Genetic and Biochemical Basis For Sweetpotato Weevil Res...supporting
confidence: 55%
“…Another study revealed similar results (with H 2 =0.49%) and further showed that additive effects contributed the most to SPW resistance and HCA concentration [51]. More recently, a narrow sense heritability (h 2 =0.30) was reported for SPW resistance based on a relatively high population [52]. We hope that the adoption of modern experimental designs such as the row-column designs, which use more replications for field phenotyping, will enable estimation of higher heritability values for SPW resistance for future genomic analyses.…”
Section: The Genetic and Biochemical Basis For Sweetpotato Weevil Res...supporting
confidence: 55%
“…In part, host plant resistance for SSA may have been difficult to achieve due to breeding tactics that lacked an appreciation of how best to approach the challenge of sweet potato genetic variation. For sweetpotato, there can be superior parental genotypes identified that favor general combining ability, but there are also specific combining abilities which can be identified when tracking a particular trait (such as SPW resistance) for crop improvement (Mugisa et al 2022). While historical trends have led some to regard SPW resistance as less likely to be achieved in SSA, some recent efforts have shown promise (Kagimbo et al 2020;Joseph et al 2022;Mugisa et al 2022).…”
Section: Host Plant Resistancementioning
confidence: 99%
“…For sweetpotato, there can be superior parental genotypes identified that favor general combining ability, but there are also specific combining abilities which can be identified when tracking a particular trait (such as SPW resistance) for crop improvement (Mugisa et al 2022). While historical trends have led some to regard SPW resistance as less likely to be achieved in SSA, some recent efforts have shown promise (Kagimbo et al 2020;Joseph et al 2022;Mugisa et al 2022). In at least one of these recent SSA efforts (Kagimbo et al 2020), there is indication that the germplasm resistance may be based on a mechanism in common with that found from selection efforts that were successful in the USA.…”
Section: Host Plant Resistancementioning
confidence: 99%
“…Resistant cultivars often possess distinct chemical compositions, including secondary metabolites and defensive compounds, which deter Cylas formicarius. These defensive compounds alter the flavor and nutritional value of sweet potato tubers (Stevenson et al 2009;Mugisa et al 2022). Some cultivars also possess morphological attributes that alter the feeding preference of weevils (Parr et al 2016).…”
Section: Introductionmentioning
confidence: 99%